TRANSLATION TECHNIQUES ON ENGLISH SEXUAL EUPHEMISMS IN DUKE OF HER OWN - Anita Anita; Defi Julianti (Asosiasi Dosen Muda Indonesia, 2023)
People tend to use euphemisms to replace words, phrases, and clauses the will make them to lose face. Euphemisms are used for certain topics, one of them is sex. Sex is considered taboo in most of societies including English and Indonesian. However, the cultures of the two societies have different point of view about sex. This is one of the difficulties that a translator must face when translating sexual euphemisms from English into Indonesian. A translator will apply certain techniques to make a translation sounds natural. This study aims at describing the translation techniques that are used by a translator in transferring English euphemisms into Indonesian. The source of the data is a novel by Eloisa James, Duke of Her Own and its Indonesian version Pasangan Sempurna. The study uses descriptive qualitative method in analyzing data. The result found that from 96 data of euphemisms, 48 data are translated using established equivalent, 12 data are translated using literal, 11 data are translated using discursive creation, 6 data are translated using explication, 5 data are translated using description, 3 data are translated using generalization.